Caracterización, inclusión y participación de la mujer Policía en la provincia de Manabí, República del Ecuador - Barén Merino, María Belén (2024)
The purpose of this study was to determine institutional actions for inclusive and participatory work in the National Police in Manabí province. To collect the information, three methods were used; inductive, deductive, analytical-synthetic; which were useful to obtain data regarding the existing problems. In addition, field, bibliographic and descriptive research was used. On the other hand, an interview was carried out, directed to the Colonel of the Manabí sub-zone, an instrument that helped to be in direct contact with the study phenomenon. In this research, we worked with a sample of the population, to whom a survey represented in a Google forms questionnaire structured in ten items was applied, with scores from one to five depending on analyzing the identified variable; as a notable result, the population of women surveyed considers the need to actively participate in the workplace, especially in the national police, since their inclusion and participation motivates those of their sex to perform the same functions.